Strengthening delivery platforms of national nutrition programs in subnational geographies in India improved coverage of interventions and child growth - Gune, Soyra; Alderman, Harold; Avula, Rasmi; Nguyen, Phuong Hong; Chakrabarti, Suman (Elsevier, 2024)
Objectives: Between 2016 and 2020, novel system strengthening mechanisms were implemented in 63.9% (N=409) of India’s districts by the government in collaboration with multiple partners to enhance the delivery of essential nutrition interventions for women and children during the critical first 1,000 days. We evaluated the influence of these mechanisms on the coverage of interventions and child growth outcomes.